The Effect of the Course Review Horay Learning Model on Students’ Motivation and Learning Outcomes - Andini, Selfi Rahmi; Miaz, Yalvema (Jurnal Pendidikan Indonesia, 2022)
The model used is still a conventional approach, it is found that students are still often in and out of class while learning is still ongoing because students' learning motivation is relatively low, often conversing with friends when learning begins, and often disturbing friends. This study aims to analyze the effect of the Course Review Hooray (CRH) learning model on the motivation and learning outcomes of fifth grade students. This research uses a quantitative approach with the Quasi Experimental method. This research uses Nonequivalent Control Group Design. This study has a sample selected by using Non-Probability Sampling. The sample for the experimental class and control class consisted of 14 students. The results showed that the acquisition of the t test of high learning motivation obtained t-count more than t-table, namely 12.89152 more than 2.056, then h0 was rejected and h1 was accepted. Then, the application of the CRH model also affects student learning outcomes which is also proven by the t test. The result of the calculation is t-count more than t-table, which is 9.926846 more than 2.056, so it can be concluded that the CRH learning model has an influence on the learning outcomes of fifth grade students.